Museum specimens reveal a rare new characid fish genus, helping to refine the interrelationships of the Probolodini (Characidae: Stethaprioninae). Issue 8 (17th November 2021) - Frainer, Guilherme; Carvalho, Fernando R.; Bertaco, VinÍCius A.; Malabarba, Luiz R.
Abstract : (Received 7 July 2021; accepted 23 September 2021) Two new characid fish species are described from the upper rio Tocantins basin, Chapada dos Veadeiros, Goiás State, Brazil. Both species were discovered among specimens in museum collections. Relationships of taxa were evaluated in a more comprehensive phylogenetic analysis utilizing the largest dataset available of molecular and morphological data for the family Characidae. The two species were recovered as sister species and described in a new genus, closely related to Erythrocharax and Phycocharax . Dinotopterygium gen. nov. is distinguished from all other characid genera by the unique combination of ten synapomorphies, including the unique anal-fin morphology with a small number of branched anal-fin rays (13-16). Dinotopterygium uniodon sp. nov. and D. diodon sp. nov. differ by the number of tooth series in the premaxillary bone (one or two) and number of tooth cusps (7 or 5). The additional phenotypic variation for a taxonomically informative character within the Characidae through the discovery of new forms has helped to refine the interrelationship of the tribe Probolodini (Characidae: Stethaprioninae). The discovery of these new and possibly critically endangered species emphasizes the importance of museum collections for understanding biodiversity past and present. http://zoobank.org/urn:lsid:zoobank.org:pub:E0FD8207-590B-4FF7-B9CA-FD481A7F8B0E